A combined study on structural, magnetic and specific heat on double perovskite iridates Ln2CoIrO6 [Ln = Pr, Nd]. (29th March 2023) - Datta, Raktim; Pradhan, Suman Kalyan; Saha, Rafikul Ali; Kumar, Ravi; Majumdar, Subham; De, Subodh Kumar
Abstract: We report rich magnetic behavior for Co–Ir based double perovskites consisting of different rare earth cations Pr and Nd: Pr2 CoIrO6 (PCIO) and Nd2 CoIrO6 (NCIO). Both oxides show an antisite disorder of 10% and a ferrimagnetic transition, T F i M around 96 K and 98 K respectively. The long range magnetic ordering is arising from the canted antiferromagnetic ordering between the Co 2+ and Ir 4+ ions. A prominent peak around 27 K in magnetization data of NCIO indicates that the total moment of Nd ion is antiferromagnetically coupled to the Co–Ir sublattice. The long range order of the Nd sublattice is corroborated by the evidence of an anomaly in specific heat at very low temperature. The compounds exhibit a maximum change of magnetic entropy of 0.57 (0.48) J kg.K −1 at T F i M in a magnetic field of 5 T. The strong spin–orbit coupling in 5 d states of Ir and cation disorder lead to the Mott insulating phase as found from the analysis of temperature dependent resistivity. These unique behaviors suggest an interesting interplay between localized Pr/Nd-4 f, itinerant Co-3 d and Ir-5 d electrons.